2021
DOI: 10.1002/adbi.202101018
|View full text |Cite
|
Sign up to set email alerts
|

Inertial Microfluidic Purification of CAR‐T‐Cell Products

Abstract: Chimeric antigen receptor T (CAR‐T) cell therapy is rapidly becoming a frontline cancer therapy. However, the manufacturing process is time‐, labor‐ and cost‐intensive, and it suffers from significant bottlenecks. Many CAR‐T products fail to reach the viability release criteria set by regulators for commercial cell therapy products. This results in non‐recoupable costs for the manufacturer and is detrimental to patients who may not receive their scheduled treatment or receive out‐of‐specification suboptimal fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 57 publications
1
2
0
Order By: Relevance
“…The first factor is the different proliferation behaviors across the outputs. As shown in Figure 3c and represented in previous work, 30 separation of larger T cells provides a population with better viability and improved proliferation rate. In the case of the IW output, most T cells would have a good proliferation rate, whether it is activated (transducible) or unactivated (not transducible).…”
Section: ■ Results and Discussionsupporting
confidence: 59%
See 2 more Smart Citations
“…The first factor is the different proliferation behaviors across the outputs. As shown in Figure 3c and represented in previous work, 30 separation of larger T cells provides a population with better viability and improved proliferation rate. In the case of the IW output, most T cells would have a good proliferation rate, whether it is activated (transducible) or unactivated (not transducible).…”
Section: ■ Results and Discussionsupporting
confidence: 59%
“…[16][17][18]23,28,29 Another key work by Elsemary et al presented a spiral inertial microfluidic purification device specifically designed for CAR T cell products. 30 Their study aimed to purify T cells to achieve higher viability by removing nonviable cells. The results indicated that the larger T cell population obtained from the developed device exhibited significantly improved viability for both untransduced T cells and CAR T cells.…”
Section: ■ Introductionmentioning
confidence: 99%
See 1 more Smart Citation